Standards in pancreatic surgery - Beger, Hans G; Büchler, Markus (Springer, 1993)
This book deals with all aspects of surgery of the pancreas. The leading authorities from all over the world have contributed to this volume. Surgery of acute pancreatitis, chronic pancreatitis and pancreatic malignancies is demonstrated. This book defines standards for pancreaticand general surgeons. In addition all aspects of diagnostics, pathophysiology and basic scientific data with regard to pancreatic disease are presented.
Keywords: pankreas - nemoci - terapie chirurgická - příručky; endokrinologie; chirurgie; gastroenterologie